2019
DOI: 10.3390/v11060571
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus DNA Detection in Respiratory Samples: Study of a Cohort of Patients Affected by Cystic Fibrosis

Abstract: Background: The role of Merkel cell polyomavirus (MCPyV) as a respiratory pathogen is controversial, and it is still unclear in patients with cystic fibrosis (CF). The aim of this study was to define the MCPyV prevalence and epidemiology in CF patients in order to gain new insights into the association between MCPyV infection and respiratory diseases. Methods: A one-year study was conducted testing oropharyngeal aspirate samples from 249 and 124 CF and non-CF patients, respectively. Detection of MCPyV was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In contrast to NCCR analysis conducted on rectal swabs from an HIV-1-positive population, which were characterized by the onset of transitions, transversions, and single or double deletions [110], MCPyV NCCR in stool samples from patients with hematological disorders exhibited a high degree of sequence stability, thereby suggesting that sequence rearrangements occurred rarely in the gastrointestinal anatomical site [113]. To date, although it is well documented that MCPyV DNA has been detected in the upper and lower respiratory tract specimens of children and adults and in immunocompetent and immunocompromised patients [114][115][116][117][118] and that the detection of MCPyV DNA was also observed in cystic fibrosis patient respiratory secretions [119,120], the respiratory NCCR structure organization has not yet been investigated.…”
Section: Mcpyv Nccr Variantsmentioning
confidence: 99%
“…In contrast to NCCR analysis conducted on rectal swabs from an HIV-1-positive population, which were characterized by the onset of transitions, transversions, and single or double deletions [110], MCPyV NCCR in stool samples from patients with hematological disorders exhibited a high degree of sequence stability, thereby suggesting that sequence rearrangements occurred rarely in the gastrointestinal anatomical site [113]. To date, although it is well documented that MCPyV DNA has been detected in the upper and lower respiratory tract specimens of children and adults and in immunocompetent and immunocompromised patients [114][115][116][117][118] and that the detection of MCPyV DNA was also observed in cystic fibrosis patient respiratory secretions [119,120], the respiratory NCCR structure organization has not yet been investigated.…”
Section: Mcpyv Nccr Variantsmentioning
confidence: 99%
“…Merkel cell polyomavirus (MCPyV) is a small, nonenveloped, double-stranded DNA virus, identified in 2008 [2] and related to the progenitors BK polyomavirus (BKPyV) and JC polyomavirus (JCPyV). Most MCPyV infections are asymptomatic, and serological studies showed that 50-80% of the healthy individuals present MCPyV-specific antibody responses [3,4]. After primary infection, HPyVs establish a lifelong persistence in different anatomical sites, such as lymphoid tissue (JCPyV), renal epithelium (JCPyV and BKPyV), and skin (MCPyV) [5].…”
Section: Introductionmentioning
confidence: 99%
“…After primary infection, HPyVs establish a lifelong persistence in different anatomical sites, such as lymphoid tissue (JCPyV), renal epithelium (JCPyV and BKPyV), and skin (MCPyV) [5]. Recently, a high prevalence of MCPyV has also been found in respiratory and stool samples from immunocompromised patients, adding important information on MCPyV prevalence and persistence in the respiratory and gastrointestinal tract [4][5][6][7][8]. MCPyV shares the genomic structure of BKPyV and JCPyV, with a circular genome divided into three functional regions: early, late, and interposed between these regions, the noncoding control region (NCCR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these conflicting rates, previous studies concordantly imply that MCPyV appears to be almost ubiquitous in the general population, which is asymptomatically infected ( 18 , 27 , 30 , 31 ). After primary infection, which occurs during childhood ( 28 , 32 , 33 ), MCPyV establishes a lifelong but inoffensive infection in healthy individuals ( 32 , 34 ). However, in certain circumstances, such as immune system impairment in the host, increased viral activity can occur.…”
Section: Introductionmentioning
confidence: 99%